Toward Greater Wellbeing: Student-Guided Strategies for Improving Sport and Recreation Engagement - Vinu Selvaratnam; Laura Wood; Ryan Snelgrove (Journal of Applied Sports Management, 2026)
Despite widespread recognition of campus recreation as a key contributor to student well-being, many university students remain underactive, even when programming is available. This study explores student-generated strategies for improving participation in campus recreation, drawing on open-ended responses from 182 undergraduates at a large Canadian university. Using thematic content analysis and chi-square comparison, we examine how suggestions differ between students who report being sufficiently active and those who do not. Seven core themes emerged, with underactive students more likely to identify structural barriers such as inconvenient scheduling, limited facility access, and insufficient communication. These suggestions are interpreted through the Leisure Constraints Model and the concept of constraint negotiation, offering insight into how students envision institutional change. Rather than passive recipients, underactive students articulated concrete strategies for engagement, highlighting the need for responsive programming that aligns with student-identified needs. The findings support a shift toward inclusive scheduling, targeted promotion, and participatory planning as mechanisms for increasing equity in campus recreation. Implications for theory, policy, and practice are discussed.
Keywords: Leisure Constraints Model; Constraint Negotiation; Physical Activity